The Resin and Carder bees of south India (Hymenoptera: Megachilidae: Anthidiini) - Kumar, Veeresh; Griswold, Terry; Belavadi, Vasuki V. (Zootaxa, 2017)
Little is known about the Anthidiini of southern India. A study focused on the state of Karnataka found a hitherto unknown diversity of thirteen species. Though the number of species is not large, the generic diversity is noteworthy (eight genera represented): Anthidiellum (2 species), Anthidium (2 species), Eoanthidium (2 species), Euaspis (2 species), Pachyanthidium (1 species), Pseudoanthidium (2 species), Stelis (1 species) and Trachusoides (1 species) are recorded from southern India. Eoanthidium tricolor Pasteels is here synonymized with E. salemense (Cockerell). The identity of a species of Anthidium (Anthidium) remains unclear. Species descriptions, floral associations, flight periods and specimen records are provided.